An Evaluation of the Psychological Factors influencing the Students’ Anxiety in Speaking English - Umisara, Elinda; Faridi, Abdurrachman; Joko Yulianto, Henrikus (Universitas Negeri Semarang, 2021)
Speaking is a productive skill that can be directly observed by considering several aspects. It can trigger the students’ anxiety as a psychological factor to communicate foreign language with others. This case has become a unique phenomenon to be analysed because anxiety has a relevance with foreign language abilities. This study aims to evaluate the psychological factor influencing the students’ anxiety in speaking English by using a qualitative approach. The data were collected by using observations, open-ended questionnaires, and interviews. There were 17 students in the ninth-grade of junior high school in Brebes Regency participating in this research. Three major phases of data analysis, namely data reduction, display, and conclusion drawing established to analyse the data. The researchers found three factors triggering the students’ anxiety in speaking English, namely communication apprehension, test-anxiety, and fear of negative evaluation which were influenced by the situation-specific anxiety. The situation could represent an uncomfortable experience emotionally and physically for some students to speak English in the class. The students felt anxious, frustrated, fearful, nervous, worried when they were unable to speak English. It made the students afraid of making mistakes and like to underestimate their abilities so that this prevents them from doing verbal activities. Therefore, this research discusses waysreduce the specific psychological factors that cause students’ anxiety in speaking English. This result can be used as guidance in managing learning conditions, learning materials, and learning strategies to deal with students’ anxiety in learning English. The teacher can use this research as a reference for analyzing the students’ anxiety symptoms during learning English in order to increase the students’ motivation and confidence in speaking performance.